Pengaruh Pendapatan Asli Daerah Dalam Mengentaskan Kemiskinan Dengan Pendekatan Fixed Effect Model - Yahya Nusa (Journal of Financial and Tax, 2024)
The purpose of this study is to analyze whether poverty alleviation in the districts/cities of Papua province can be influenced by Regional Original Income or still depends on central transfer funds. The data used in this study are Regional Original Revenue, Balancing Fund and Special Autonomy Fund obtained from the Budget Realization Report (LRA) at the Directorate General of Financial Balance (DJPK) of the Ministry of Finance. Meanwhile, poverty data is obtained from the Central Statistics Agency (BPS) of Papua province, where the data is a combination of time series data and cross section (pool data / panel data) in 29 districts/cities in Papua province during 2012-2022. The research method is panel data analysis with Fixed Effect Model (FEM) approach using EViews12. The results showed that Regional Original Income did not have a significant effect on poverty in the districts/cities of Papua province, while the Balancing Fund and Special Autonomy Fund had a significant effect on poverty in the districts/cities of Papua Province. This shows that in alleviating poverty in the districts/cities of Papua province still depends on central transfer funds, namely the balance fund and special autonomy funds. However, if the government can optimize the sources that are the basis of local original income optimally, then the role of local original income has the potential to reduce poverty in the districts/cities of Papua province.